Overcoming the Design Challenge in 3D Biomimetic Hybrid Scaffolds for Bone and Osteochondral Regeneration by Factorial Design - Dellaquila, Alessandra; Campodoni, Elisabetta; Tampieri, Anna; Sandri, Monica (Frontiers in Bioengineering and Biotechnology, 2020)
Scaffolds for bone regeneration have been engineered by a plethora of manufacturing technologies and biomaterials. However, the performance of these systems is often limited by lack of robustness in the process design, that hampers their scalability to clinical application. In the present study, Design of Experiment (DoE) was used as statistical tool to design the biofabrication of hybrid hydroxyapatite (HA)/collagen scaffolds for bone regeneration and optimize their integration in a multilayer osteochondral device. The scaffolds were synthesized via a multi-step bioinspired process consisting in HA nano-crystals nucleation on the collagen self-assembling fibers and ribose glycation was used as collagen cross-linking method to modulate the mechanical and physical properties. The process design was performed by selecting hydrogel concentration, HA/collagen ratio and cross-linker content as key variables and the fabrication was carried out basing on a full factorial design. Scaffold performances were tested by evaluating porosity, swelling ratio, degradation rate and mechanical behavior as model output responses while physicochemical properties of the constructs were evaluated by TGA, ICP, FT-IR spectroscopy, and XRD analysis. Physicochemical characterizations confirmed the nucleation of a biomimetic inorganic phase and the interaction of the HA and collagenic components. The DoE model revealed a significant interaction between HA content and collagen cross-linking in determining porosity, swelling and mechanical properties of the scaffolds. The combined effect of hydrogel concentration and mineral phase played a key role on porosity and swelling while degradation resulted to be mainly affected by the HA loading and ribose content. The model was then used to determine the suitable input parameters for the synthesis of multi-layer scaffolds with graded mineralization rate, that can be used to mimic the whole cartilage-bone interface. This work proved that experimental design applied to complex biofabrication processes represents an effective and reliable way to design hybrid constructs with standardized and tunable properties for osteochondral tissue engineering.